The adverse impact of HFpEF in patients with aortic stenosis: evaluation of the H2FPEF score for risk assessment among patients with preserved ejection fraction undergoing TAVI. (25th November 2020) - Ludwig, S; Pellegrini, C; Gossling, A; Rheude, T; Waldschmidt, L; Bhadra, O.D; Linder, M; Schirmer, J; Seiffert, M; Reichenspurner, H; Blankenberg, S; Westermann, D; et al.
Abstract: Background: The H2FPEF score enables identification of patients with high probability of prevalent heart failure with preserved ejection fraction (HFpEF). High H2FPEF scores have proven to be associated with adverse outcome in patients with known HFpEF. Objective: The aim of this study was to assess the prognostic impact of the H2FPEF score in patients undergoing Transcatheter Aortic Valve Implantation (TAVI) for severe aortic stenosis (AS) and preserved left ventricular ejection fraction (EF). Methods: In this multi-centre study a total of 832 patients from two German high-volume centres, who received TAVI for severe AS and preserved EF (≥50%), were identified for calculation of the H2FPEF score. Score variables included BMI >30 kg/m 2, arterial hypertension, atrial fibrillation, systolic pulmonary artery pressure >31 mmHg, age >60 years, and invasively assessed elevated LV filling pressure. Patients were dichotomized according to low (1–5 points; n=570) and high H2FPEF scores (6–9 points; n=262). Kaplan-Meier and Cox regression analyses were applied to assess the prognostic impact of the H2FPEF score. Median follow-up time was 1.08 years. Results: Patients presenting with high H2FPEF scores had higher prevalence of moderate to severe mitral and tricuspid regurgitation compared to those with low H2FPEF scores. Stroke volume index (SVI) (Figure 1A) and mean transvalvular gradient (Pmean) consistently decreased with increasing H2FPEF score. All-cause mortality 30 days after TAVI was significantly higher in patients with high H2FPEF scores (p<0.0001). This finding was consistent both after 1 year (p<0.0001) and 3 years (p<0.0001) (Figure 1B). Multivariate analysis revealed a high H2FPEF score to be independently predictive for all-cause mortality (HR 1.62, 95% CI: 1.11–2.38, p=0.013). Among the single H2FPEF score parameters atrial fibrillation was the strongest independent predictor of adverse outcome. Conclusion: An elevated H2FPEF score of ≥6 is independently predictive for mortality in patients with preserved EF undergoing TAVI for severe AS, which might be due to a higher proportion of paradoxical low flow low gradient AS in these patients. Our findings provide evidence that the H2FPEF score may help identify AS patients with preserved ejection fraction that are at higher risk for adverse outcome after TAVI. Funding Acknowledgement: Type of funding source: None